Assessment of asymmetry and trajectory during repeated twenty-meter sprints in court sports wheelchair athletes - Brassart, F.; Bakatchina, S.; Alberca, I.; Pomarat, Z.; Watelain, E.; Weissland, T.; Faupin, A. (Frontiers in Sports and Active Living, 2025)
Introduction: Manual wheelchair (MWC) propulsion relies on upper limb power, coordination, and endurance. Propulsion asymmetry can reduce efficiency, yet the impact of fatigability on upper limb asymmetry remains underexplored. This study aimed to compare propulsion performance and asymmetry between wheelchair basketball (WB) and wheelchair rugby (WR) players and assess the effect of fatigability on asymmetry during repeated sprints.